Mineral chemistry and petrology of mantle peridotites from the Guleman ophiolite (SE Anatolia, Turkey): Evidence of a forearc setting. (November 2016) - Rizeli, Mustafa Eren; Beyarslan, Melahat; Wang, Kuo-Lung; Bingöl, A. Feyzi
Abstract: The mantle section of Guleman ophiolite, southeast (SE) Turkey consists mainly of harzburgites and dunite lenses and large chromitite pods. The average Cr ratio = [100 × Cr/(Cr + Al) atomic ratio] of Cr-spinels in harzburgites and dunites is remarkably high (>63). The forsterite (Fo) content of olivine is between 90.9 and 92.3 in harzburgites and dunites. These features indicate that the harzburgites and dunites resulted from >35% of partial melting of a depleted mantle source. Discriminant geochemical diagrams based on the mineral chemistry of harzburgites indicate a supra-subduction zone (SSZ) origin. Orthopyroxene and clinopyroxene from the Guleman harzburgites have low CaO, Al2 O3 and TiO2 contents, resembling those of depleted harzburgites from modern forearcs and contrasting with moderately depleted abyssal peridotites. Consequently, we propose that the Guleman peridotites formed in a forearc setting during the subduction initiation that developed as a result of northward subduction of the southern branch of the Neo-Tethys in response to the convergence between the Arabian and Anatolian plates. Highlights: The Guleman mantle peridotites consist of mainly harzburgites. They are restites of a high degree melted of upper mantle. The Guleman mantle peridotites developed as a result of northward subduction of the southern branch of the Neo-Teyhys.